Penggunaan Video Animasi dalam Pembelajaran Pendidikan Agama Islam Pada Siswa Kelas 1 Sekolah Dasar - Muhammad Rohan Saputra; Kautsar Eka Wardhana; Rahmad Effendy; Rahmatul Muthmainnah; Trianisa Ayu Anastasya (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2021)
Along with the times, technology has also developed, many changes have occurred because of technology, such as in the fields of health, agriculture, education and many other fields. Therefore, in the world of education, we must continue to keep up with the times so that the field of education is not left behind by other fields. We know that education is very influential for the progress of a country. The teacher's responsibility is very large in it, all teachers should not be easily satisfied with what they have now, but must continue to learn to keep up with increasingly advanced technological developments. Today's learning media are very much like animated videos that can be applied at several levels of education. Using media in the form of animated videos in the learning process at the elementary school education level is an effective thing because at their age they are very happy when they see something different. Previously their learning process only used media in the form of textbooks or notebooks which might cause boredom to students but with the development of very advanced technology the learning process can use animated videos, but that does not mean to replace books as teaching materials but instead integrate teaching materials so that students do not feel bored. The purpose of education is essentially to humanize humans. If we want students not to feel bored and be able to continue to understand the learning material provided, a teacher must be good at implementing a learning system, starting from determining teaching materials to the methods used, a teacher must also be able to attract the attention of participants. educate them by giving something new because elementary school children will be easily interested if they see something different.